Mastering AngularJS for .NET developers : master the art of developing applications using AngularJS, ASP.NET Web API 2, and Visual Studio 2013 /: master the art of developing applications using AngularJS, ASP.NET Web API 2, and Visual Studio 2013. (2015) - Majid, Mohammad Wadood; Mirzaei, Golrokh
No abstract available